Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Please help me to solve this problem.I can not understand what to do.
If $(a^2-b^2)\sin\theta + 2ab\cos\theta = a^2+b^2$ and $\theta$ is acute and positive angle then what is the value of $\tan\theta$ and $\csc\theta$ ?

share|cite|improve this question


$$(a^2-b^2)\sin\theta + 2ab\cos\theta = (a^2+b^2)\sin(\theta+\alpha)$$


$$\cos(\alpha)=\frac{a^2-b^2}{a^2+b^2},\ \sin(\alpha)=\frac{2ab}{a^2+b^2}$$

share|cite|improve this answer

Hint for one possible solution: As in the tangent half-angle substitution, let $t = \tan\frac\theta2$; then $\sin\theta = 2t/(1+t^2)$ and $\cos\theta = (1-t^2)/(1+t^2)$. Substituting these into your equation and simplifying will yield a quadratic in $t$. Solve for $t$, then use the tangent double-angle identity to get $\tan\theta$.

share|cite|improve this answer

Your equation can be written

$$\frac{1-t^2}{1+t^2} \sin \theta + \frac{2t}{1+t^2}\cos \theta = 1$$

Where $t = \frac b a$.

Now, if $\frac b a = t=\tan \frac{\alpha}{2}$ (with $\alpha \in ]0, \pi[$ if both $a$ and $b$ are positive), then $\frac{1-t^2}{1+t^2}=\cos \alpha$ and $\frac{2t}{1+t^2}=\sin \alpha$, and the equation becomes:

$$\cos \alpha \sin \theta + \sin \alpha \cos\theta = 1$$


$$\sin (\alpha + \theta) = 1$$

You get $\theta = \frac{\pi}2 - \alpha + 2k\pi$, thus $$\tan \theta = \frac{1}{\tan \alpha} = \frac {\cos \alpha}{\sin \alpha}=\frac{a^2-b^2}{2ab}$$


$$\csc \theta = \frac{1}{\sin \theta} = \frac{1}{\cos \alpha} = \frac{a^2+b^2}{a^2-b^2}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.